Evaluation of an alternative technique to optimize direct bonding of orthodontic brackets to temporary crowns - Francilena Maria Campos Santos Dias; Célia Regina Maio Pinzan-Vercelino; Rudys Rodolfo de Jesus Tavares; Júlio de Araújo Gurgel; Fausto Silva Bramante; Melissa Nogueira Proença Fialho (Dental Press Editora, 2015)
OBJECTIVE: To compare shear bond strength of different direct bonding techniques of orthodontic brackets to acrylic resin surfaces.METHODS: The sample comprised 64 discs of chemically activated acrylic resin (CAAR) randomly divided into four groups: discs in group 1 were bonded by means of light-cured composite resin (conventional adhesive); discs in group 2 had surfaces roughened with a diamond bur followed by conventional direct bonding by means of light-cured composite resin; discs in group 3 were bonded by means of CAAR (alternative adhesive); and discs in group 4 had surfaces roughened with a diamond bur followed by direct bonding by means of CAAR. Shear bond strength values were determined after 24 hours by means of a universal testing machine at a speed of 0.5 mm/min, and compared by analysis of variance followed by post-hoc Tukey test. Adhesive remnant index (ARI) was measured and compared among groups by means of Kruskal-Wallis and Dunn tests.RESULTS: Groups 3 and 4 had significantly greater shear bond strength values in comparison to groups 1 and 2. Groups 3 and 4 yielded similar results. Group 2 showed better results when compared to group 1. In ARI analyses, groups 1 and 2 predominantly exhibited a score equal to 0, whereas groups 3 and 4 predominantly exhibited a score equal to 3.CONCLUSIONS: Direct bonding of brackets to acrylic resin surfaces using CAAR yielded better results than light-cured composite resin. Surface preparation with diamond bur only increased shear bond strength in group 2.